THE URGENCY OF COOLING-OFF PERIOD CLAUSE IN INVESTOR-STATE DISPUTE SETTLEMENT : GOOD FAITH NEGOTIATION - Deriandy, Jesslyn Febria (Transnational Business Law Journal, 2023)
With the development of foreign direct investors, international investment treaties also becoming more popular, causing more cases are occurring from said treaties. To deal with disputes, international investment treaties have dispute settlement mechanisms. Investor-State dispute settlement mechanisms in international investment treaties often include cooling-off clauses. In each case, the arbitral tribunal made different decisions regarding the compliance of this clause, provoking much controversy. Often, the cooling-off period is waived by the claimant since there is no clear motive regarding the urgency. The aim of this article is to determine the urgency of the cooling-off period clauses in bilateral investment treaties as a precondition for arbitration. The method for research used in this study is descriptive analysis. The authors also use primary legal material, such as international arbitration, bilateral investment treaties, and arbitration rules. In addition, the authors use secondary legal sources such as related literature and journals. Based on the findings of this study, the existence of a cooling-off period clause plays a role in enabling parties to discuss their disputes in good faith before submitting them to international arbitration.